Synthesis of High-Performance Antibacterial Magnesium Oxide Nanostructures through Laser Ablation - Sara Abbas; Adawiya Hadier; Sharafaldin Al-Musawi; Bakr Taha (Journal of Applied Sciences and Nanotechnology, 2024)
In this study, we synthesized magnesium oxide (MgO) nano flakes (NFs) through pulsed laser ablation of magnesium ribbons, investigating their potent antibacterial properties for potential biomedical applications. Thorough characterization utilizing advanced analytical techniques verified the phase purity and functionality of the fabricated MgO NFs. Results revealed a distinctive flake-like structure with an average diameter of 100-400 nm and a slender wall thickness of 24 nm. The efficiency of the laser ablation method was validated by EDX imaging, showing high purity in the MgO sample. XRD analysis further confirmed the polycrystalline nature of MgO NFs, with dominant peaks at 2θ values of 38.86°, 59.46°, 62.83°, and 73.87° corresponding to (111), (110), (220), and (311) diffractions, respectively. UV-visible spectroscopy exhibited a broad absorption peak, and Tauc's formula yielded an energy band gap of 5.8 eV. FTIR spectroscopy detected Mg–O–Mg bending vibration, O−H stretching vibration, O=C=O stretching, and O−H bending vibration. Optimized MgO-NFs demonstrated remarkable antibacterial efficacy against both gram-positive Staphylococcus aureus (S. aureus) and gram-negative Escherichia coli (E. coli) bacteria. Maximum antibacterial activity was observed at a high MgO NFs concentration (200 µg/ml), resulting in 15 mm ±0.5 mm and 16 mm ±0.5 mm inhibition zones for E. coli and S. aureus, respectively. The minimum inhibitory concentration (MIC) for both pathogens was determined to be 25 µg/ml, emphasizing the promising antimicrobial potential of the MgO NFs.